Implementation of Strengthening the Profil Pelajar Pancasila in Student Character Development - Iffatul Lailiyah; Umi Azizah; Alfoyatin Mutoharoh; Latifatul Maulidiyah (AJER: Advanced Journal of Education and Religion, 2024)
The things that form the background for the formation of the Pancasila student profile are character educators who are starting to erode with time and are increasingly being forgotten. It is in this character education that students of Pancasila are realized who become the profile of the Indonesian nation in the national and international spheres. The Ministry of Education and Culture stated that "Indonesian students are students who are always competent, have character, and achieve according to Pancasila values." In addition, the Pancasila Student Profile has the following six abilities; “1) Having faith, piety to God Almighty, and having noble character; 2) Global diversity; 3) Working together; 4) Independent; 5) Critical reasoning; 6) Creative.” These six abilities reinforce each other so that efforts to create a Pancasila Student Profile can develop as a whole. The purpose of this research is that students can implement the dimensions contained in the Pancasila Student Profile Strengthening Project and can apply their character according to the Pancasila Student Profile. This research was conducted at SMK Negeri 1 Kalitengah Jalan Mahkota No. 280 Dibee Kalitengah Lamongan. The choice of location for this study was based on the researcher's interest in building the character of the students of SMK Negeri 1 Kalitengah through the Pancasila Student Profile Strengthening Project using a qualitative research approach. The data collection techniques used in this study are: Observation, Interview and Documentation